PENERAPAN ASAS TABELLIONIS OFFICIUM FIDELITER EXERCEBO DALAM PENANDATANGANAN AKTA NOTARIS SECARA DIGITAL - Kartika, Rifda Salma; Lintang Saskia Salsabella; Angelica Ratih Kusumadewi (PERSPEKTIF : Kajian Masalah Hukum dan Pembangunan, 2024)
The development of information and communication technology requires the law to move dynamically along with developments in time and technology. There is a principle used by Notaries in carrying out their duties and positions, namely the Tablelionis Officium Fideliter Exercebo Principle, the principle which states that Notaries must work traditionally. There is a problem formulation, namely the Influence of Digital Signatures on the Obligations and Authorities of Notaries Based on the Tablelionis Officium Fideliter Exercebo Principle. The approach used is a statutory approach (statue approach) and a contextual approach (conceptual approach). The basis for applying digital signatures is contained in article 1 number 12 of the ITE Law and article 1 number 22 of PP PSTE which has legal force and legal consequences, at the General Meeting of Shareholders (GMS) carried out virtually. Digital signatures in e-rups have fulfilled the requirements in the ITE Law. Making e-rups by a Notary must also not violate the principle of the principle of the Tablelionis Officium Fideliter Exercebo principle.